Refugee resettlement in the United States
1 online resource
Keywords: "This book focuses on refugee resettlement in the post-9/11 environment of the United States with theoretical work and ethnographic case studies that portray loss, transition, and resilience. Each chapter unpacks resettlement at the macro or micro scale, underscoring the multiple, and mostly unsupported, negotiations refugees must undertake in their familial, social, educational, and work spheres to painstakingly reconstruct and reintegrate their lives. The contributors show how civil society groups and individuals push back against xenophobic policies and strive to support refugee communities, and how agentive efforts result in refugees establishing stable lives, despite punishing odds. This volume will be of interest to anthropologists and other scholars with a focus on refugee and migration studies"--